2013
DOI: 10.1002/ajh.23526
|View full text |Cite
|
Sign up to set email alerts
|

Rapid donor T‐cell engraftment increases the risk of chronic graft‐versus‐host disease following salvage allogeneic peripheral blood hematopoietic cell transplantation for bone marrow failure syndromes

Abstract: The risk of graft-rejection after allogeneic hematopoietic cell transplantation using conventional cyclophosphamide-based conditioning is increased in patients with bone marrow failure syndromes (BMFS) who are heavily transfused and often HLA-alloimmunized. Fifty-six patients with BMFS underwent fludarabine-based reduced-intensity conditioning and allogeneic peripheral blood progenitor cell (PBPC) transplantation at a single institution. The conditioning regimen consisted of intravenous cyclophosphamide, fluda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The increase in GVHD observed with PBSC transplants is probably due to these grafts containing an average 20-fold higher dose of T-cells that have undergone granulocyte colony-stimulating factor (G-CSF)-induced T-helper cell type 2 (Th2) cytokine polarization (Ferrara & Krenger, 1998;Sloand et al, 2000;Skert et al, 2009). Furthermore, with PBSC transplantation for SAA, rapid donor T-cell engraftment frequently occurs, which is significantly associated with an increased risk of chronic GVHD (Pantin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increase in GVHD observed with PBSC transplants is probably due to these grafts containing an average 20-fold higher dose of T-cells that have undergone granulocyte colony-stimulating factor (G-CSF)-induced T-helper cell type 2 (Th2) cytokine polarization (Ferrara & Krenger, 1998;Sloand et al, 2000;Skert et al, 2009). Furthermore, with PBSC transplantation for SAA, rapid donor T-cell engraftment frequently occurs, which is significantly associated with an increased risk of chronic GVHD (Pantin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Acute GVHD was graded using established criteria (Przepiorka et al , ). Chronic GVHD was evaluated prospectively based on National Institutes of Health consensus criteria (Filipovich et al , ) and was retrospectively reclassified as limited or extensive for comparison between patients in this study and a cohort of previously reported BMFS patients who received an unmanipulated PBSC transplant using the identical conditioning regimen and GVHD prophylaxis (Pantin et al , ). Overall survival was defined as the time from transplantation to death from any cause.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have shown that a transplant regimen utilizing cyclophosphamide, fludarabine, and equine ATG conditioning with a G-CSF-mobilized PBSC transplant results in excellent engraftment and survival in heavily transfused SAA patients who have failed prior immunosuppressive therapy. However, this regimen often results in very rapid donor T cell engraftment, which was recently shown to be an independent variable in a multivariate analysis increasing the risk of chronic GVHD [ 14 ].…”
Section: Discussionmentioning
confidence: 99%